Differential Roles of Orexin Receptors in the Regulation of Sleep/Wakefulness - Mieda, Michihiro; Tsujino, Natsuko; Sakurai, Takeshi (Frontiers in Endocrinology, 2013)
Orexin A and orexin B are hypothalamic neuropeptides that play critical roles in the regulation of sleep/wakefulness, as well as in a variety of physiological functions such as emotion, reward, and energy homeostasis. The actions of orexins are mediated by two receptors, orexin 1 (OX1R) and orexin 2 (OX2R) receptors. OX1R and OX2R show partly overlapping but distinct distributions throughout the central nervous system, suggesting their differential roles. This review presents and discusses the current knowledge concerning the physiological roles of each orexin receptor subtype, focusing on the regulation of sleep/wakefulness.